PENGARUH MEDIA MATH BINGO TERHADAP HASIL BELAJAR MATERI RASIO KELAS V SDN LARANGAN SORJAN 2 - Mauliyana; Zahrani Susilo, Claudya (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
The use of innovative learning media is essenstial in helping students comprehend abstract mathematical concepts, including ratio. One of the media that can be utilized is Math Bingo, whish is designed to create an interactive and engaging learning environtment. This  study aims to describe the influence of Math Bingo on the learning outcomes of fifth  grade students at SDN Larangan Sorjan 2 Klampis Bangkalan in ratio material. The research method employed is a quasi experimental design with a pretest postest control group, involving a sample of 27 fifth grade students at SDN Larangan Sorjan 2 Klampus Bangkalan. Data were collected through observation, interviews, and pretest-postetst techniques. Analysis using t-test yielded a t-value of 1.705619, and with t-table value at df 26 and a significance level of 0,05 being 0,00000030, t-calculated >t-table (1,705619>0,00000030). Additionally, the significance level was less than 0,05 (0,00000030 < 0,05). Thus, according to the t-test criteria , H0 is rejected, and H1 is accepted, indicating a significant influence on the learning outcome of fofth grade students at SDN Larangan Sorjan 2 Klampis Bangkalan